A moderate 500-m treadmill walk for estimating peak oxygen uptake in men with NYHA class I-II heart failure and reduced left ventricular ejection fraction - Gianni Mazzoni; Biagio Sassone; Giovanni Pasanisi; Jonathan Myers; Simona Mandini; Stefano Volpato; Francesco Conconi; Giorgio Chiaranda; Giovanni Grazzi (BMC Cardiovascular Disorders, 2018)
Abstract Background Maximal cardiopulmonary exercise testing (CPX) is the gold-standard for cardiorespiratory fitness assessment in chronic heart failure (CHF) patients. However, high costs, required medical supervision, and safety concerns make maximal exercise testing impractical for evaluating mobility-impaired adults. Thus, several submaximal walking protocols have been developed and currently used to estimate peak oxygen consumption (VO2peak) in CHF patients. However, these tests have to be performed at close to maximum exercise intensity. The aim of this study was to examine the validity of a 500-m treadmill-walking test carried out at moderate intensity for estimating VO2peak in community-dwelling adult and elderly patients with CHF and reduced left ventricular ejection fraction (HFrEF). Methods Forty-three clinically stable men with HFrEF (age 67.7 ± 9.2 years, and left ventricular ejection fraction, LVEF 38% ± 6%) underwent exercise testing during an outpatient cardiac rehabilitation/secondary prevention program. Each patients completed a CPX, and a moderate and self-paced (11–13/20 on the Borg scale) 500-m treadmill-walking test. Age, weight, height, walk time, and heart rate during the 500-m test were entered into prediction equations previously validated for VO2peak estimation from a 1000-m walking test in patients with cardiovascular disease and preserved LVEF. Results Directly measured and estimated VO2peak values were not different (21.6 ± 4.9 vs 21.7 ± 4.6 mL/kg/min). The comparison between measured and estimated VO2peak values yielded a correlation of R = 0.97 (SEE = 0.7 mL/kg/min, P < 0.0001). The slope and the intercept coincided with the line of identity (Passing and Bablock analysis, P = 0.50). Residuals were normally distributed, and the examination of the Bland-Altman analysis do not show systematic or proportional error. Conclusions A moderate and self-regulated 500-m treadmill-walking test is a valid tool for VO2peak estimation in patients with HFrEF. These findings may have practical implications in the context of transitioning from clinically based programs to fitness facilities or self-guided exercise programs in adults and elderly men with HFrEF.